Enterprise Architecture Design Using TOGAF Adm at PT. Industri Telekomunikasi Indonesia - Heri Aji Setiawan; Andi Naila Quin Azisah Alisyahbana; Arnes Yuli Vandika; Bambang Prihantoro Nugroho; Ikhwanto Asri (Indonesian Journal of Enterprise Architecture, 2024)
Telecommunications company PT. Industri Telekomunikasi Indonesia (INTI) has several main business lines, such as manufacturing and assembly, management services, digital services, and system integrators. The system integrator requires assistance from all business divisions to support its business activities, one of which is to assist the information technology function, which is responsible for information technology services. However, there are several obstacles that arise in the implementation of the information technology function, including data exchange that has not used the system optimally; lack of manpower; business process flow that is still less effective; and one business process that is still less effective and has not been supported by existing applications. The existing applications are not integrated. Thus, the right solution and in accordance with the needs must be generated through an enterprise architecture that can integrate information technology strategy with business strategy. TOGAF ADM is used to design enterprise architecture, which includes preliminary, architecture, and implementation phases.